2х+17=22+3х
2х-3х=22-17
- х=5
х= - 5
18 + 3х=х+14
3х-х=14-18
2х= - 4
х = -2
25-4х=12-5х
-4х+5х=12-25
х=-13
13х+27=16х+4,5
13х-16х=4,5-27
-3х=-22,5
х=7,5
21х+45=17+14х
21х-14х=17-45
7х= - 28
х= - 4
13х+70=2х+15
13х-2х=15-70
11х=-55
х=-5
3х-1=2(х-2)
3х-1=2х-4
3х-2х=-4+1
х=-3
3(х+5)=7-5х
3х+15=7-5х
3х+5х=7-15
8х=-8
х=-1
19(у-9)=3(у+7)
19у-171=3у+21
19у-3у=171+21
16у=192
у=12
4(х-9)=3(х-8)
4х-36=3х-24
4х-3х=-24+36
х=12
3(2х-9)=5(х-4)
6х-27=5х-20
6х-5х=-20+27
х=7
7(3-2х)=15(1-х)
21-14х=15-15х
-14х+15х=15-21
х=-6
7х-(3+2х)=х+9